NON-PHARMACOLOGICAL INTERVENTIONS TO OVERCOME POSTOPERATIVE FATIGUE - Nugraha, Bambang Aditya; Ramdhanie, Gusgus Ghraha; Sulastini, Sulastini (Karsa Husada Health Institute Garut, 2024)
Surgery is a medical procedure that involves invasive actions on certain parts of the body. Fatigue is often experienced by postoperative patients related to changes in hemodynamic status, sedation and so on. It is essential to manage postoperative fatigue in order to prevent delayed recovery and improve quality of life. This literature review aims to identify the nonpharmacological intervention to managing postoperative fatigue. The method use was a narrative review study, The review was conducted several databases ScienceDirect, PubMed, Springer, Sagepub and google scholar, to search data from 2018 to 2024. The keywords used were nonpharmacologic intervention and postoperative fatigue. The results of this study retrieved nine articles reviewed, which were eight article randomized control trials and one article quasi experimental. The review found that the interventions to manage postoperative fatigue are progressive muscle relaxation, Benson relaxation and early exercise. Based on the results of the review, it was found that every specific interventions on specific subject were proven to overcome postoperative fatigue. The study findings provide information for nurses regarding postoperative fatigue management in order to improve the quality of life.